2017
DOI: 10.1007/978-1-4939-6848-0_22
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Colorimetric PCR-Based Biosensor for Detection and Quantification of Hepatitis B Virus

Abstract: We have established an operationconvenient and cost-effective way for detection HBV. This method has shown good performance with a broad range of linearity and high sensitivity. The results of detection is reported with macroscopic colorimetric signals. The strategy takes the key advantage of the TaqMan technology and use inexpensive DNA sensor. This approach can detect HBV DNA qualitatively or quantificationally. Hepatitis B virus (HBV) can cause viral infection that attacks the liver and it is a major global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 56%
“…We followed a previous strategy of tagging the 5 ′ end of the primers with sequences complementary to the G-quadruplex which forms a G-quadruplex only upon amplification of the PCR product (Bhadra et al, 2014). A similar strategy has been employed for the detection of viruses such as hepatitis B virus and to detect the HIV-1 gag gene by other studies previously (Yang et al, 2017;Kim et al, 2018). We employed this approach to detect SARS-CoV-2 RNA by conventional PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Visual nucleic acid detection has attracted much attention due to its simplicity, high sensitivity, and visual results [22,23,24,25]. For example, colorimetric detection has been reported for some animal viruses, including H1N1 influenza virus [26,27,28,29], H5N1 influenza virus [30], hepatitis B virus [31,32], Zika virus [33], and Rift Valley Fever Virus [34]. A colorimetric detection method was reported for CGMMV [35] based on unmodified gold nanoparticles, with a limited detection of 30 pg/μL of CGMMV RNA.…”
Section: Introductionmentioning
confidence: 99%